Improving Active Sentence Writing Skills Using Educandy Technology in Grade III at Nurussa'adah Islamic Elementary School - Riska Nur Holisoh; Andestend; Putri Ria Angelina (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
This study aims to improve the active sentence writing skills of third-grade students at MI Nurussa’adah, Bogor Regency, through the use of the digital learning platform Educandy. The background of the research stems from students’ low writing abilities, primarily due to monotonous conventional teaching methods and the lack of technological integration in language instruction. The research method employed is Classroom Action Research (CAR) using the Kemmis and Taggart model, which consists of two cycles involving planning, action, observation, and reflection. The study involved 26 third-grade students. Data were collected through observation, written tests, and documentation. The results showed a significant improvement in students' writing skills. In Cycle I, 22 students (84.6%) achieved the minimum mastery criteria, which increased to 100% in Cycle II. Moreover, the integration of Educandy was proven to enhance students' motivation and engagement through its interactive and enjoyable learning activities. It can be concluded that Educandy is an effective medium to enhance students’ active sentence writing skills and foster an innovative, engaging learning environment. This research recommends that teachers utilize interactive digital media to support the achievement of Indonesian language learning objectives more effectively